Retentive force of telescopic crowns combining fiber-reinforced composite and zirconia - Tasaka, Akinori; Schwindling, Franz Sebastian; Rues, Stefan; Rammelsberg, Peter; Yamashita, Shuichiro (Journal of prosthodontic research, 2022)
Purpose: This study investigated changes in the retentive force of telescopic crowns fabricated by combining a zirconia primary crown and a fiber-reinforced composite (FRC) secondary crown.Methods: Primary zirconia crowns were produced with a nominal convergence angle of 0°. Forty-eight secondary crowns were milled from FRC and divided into three study groups (n=16/group) based on milling parameters and post-milling adjustment. The offset parameter used for the final milling step of the inner crown surface was adjusted for a tight initial fit in Group 1 (milling offset: +10 µm, i.e., 2 × 10 µm = 20 µm lower inner diameter compared with the CAD file of the crown) and for improved initial fit (milling offset: -10 µm, i.e., an enlargement of the inner crown diameter by 2 × 20 µm = 40 µm in relation to Group 1) in Groups 2 and 3. The inner surfaces of the secondary crowns were polished with diamond paste in Groups 1 and 2, and silicon points were used for Group 3. The retentive force was measured using a universal testing device. The secondary crown was placed on the primary crown, with the final fitting force set to a load of 100 N. This test was conducted before and after aging (10,000 insertion/removal cycles) under dry and wet conditions. A generalized linear model was used to estimate the differences in the retentive force to elucidate the effects of the milling parameters and polishing methods.Results: We realized an initial retentive force of approximately 10 N. In Groups 2 and 3, the difference was statistically significant between the dry and wet conditions before aging (P < 0.05). There was no significant difference between the dry and wet conditions after aging in any of the groups (P > 0.05).Conclusion: An adequate initial retentive force can be achieved with telescopic crowns combining zirconia and FRC.